PENGARUH METODE TASMI’ TERHADAP KUALITAS HAFALAN AL-QUR’AN PESERTA DIDIK DI MTsN 1 KOTA MAKASSAR - Muh. Akmal; Akhmad Syahid; Mustamin; Abdul Wahab; Muh Aidil Sudarmono R (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to determine the effect of the Tasmi' method on the quality of Al-Qur'an memorization of students at MTsN 1 Makassar City. The background of this study is based on the importance of maintaining the quality of Al-Qur'an memorization through systematic and structured methods. The Tasmi' method is a learning approach that emphasizes the activity of listening to memorization to teachers or peers to get direct correction of the reading. This approach is believed to improve fluency, accuracy of tajwid, and memorization endurance of students. This study uses a quantitative approach with a correlational research type. The population in this study were all 200 students of the Tahfidz class of MTsN 1 Makassar City. The research sample consisted of 40 students from class IX Tahfidz selected through cluster random sampling techniques. Data collection techniques include questionnaires, observation, documentation, and oral memorization tests. Data analysis was carried out with descriptive and inferential statistics using the Pearson Product Moment correlation test. The results of the study showed a significant relationship between the application of the Tasmi' method and the quality of Al-Qur'an memorization of students. The percentage of influence obtained was 69.3%, while 30.7% was influenced by other factors. Thus, the more intensively the Tasmi' method is applied, the higher the quality of students' memorization, both in terms of fluency, accuracy of recitation, and consistency of memorization.